The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3747/co.v17i4.521
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Chemoradiation for Gastric Cancer with Infusional 5-Fluorouracil and Cisplatin: A Phase I Study

Abstract: ObjectiveThis phase i study aimed to determine the maximal tolerated dose of cisplatin administered every 2 weeks with infusional 5-fluorouracil (5fu) and concurrent radiation therapy (rt) in patients after complete resection of gastric adenocarcinoma. MethodsPatients with resected stage ib to iv (M0) gastric adenocarcinoma were treated with 12 weeks of infusional 5fu (200 mg/m 2 daily) and with rt (45 Gy in 25 fractions starting on day 16). Cisplatin was administered in escalating doses (0,20, 30, and 40 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…The exclusion criteria ruled out patients declining adjuvant chemoradiation or not fit for it, those found to have distant disease at the time of the operative procedure, patients with pathology other than adenocarcinoma, and those with T1N0 or T2aN0 disease. The patients received adjuvant 5-fluorouracil (FU)-based chemotherapy combined with radiotherapy (45/Gy), either according to the MacDonald protocol or as part of an institutional phase 1 study combined with radiotherapy (45 Gy/25 fractions) delivered using three-dimensional conformal or intensity-modulated radiation therapy (IMRT) techniques [17][18][19].…”
Section: Patientsmentioning
confidence: 99%
“…The exclusion criteria ruled out patients declining adjuvant chemoradiation or not fit for it, those found to have distant disease at the time of the operative procedure, patients with pathology other than adenocarcinoma, and those with T1N0 or T2aN0 disease. The patients received adjuvant 5-fluorouracil (FU)-based chemotherapy combined with radiotherapy (45/Gy), either according to the MacDonald protocol or as part of an institutional phase 1 study combined with radiotherapy (45 Gy/25 fractions) delivered using three-dimensional conformal or intensity-modulated radiation therapy (IMRT) techniques [17][18][19].…”
Section: Patientsmentioning
confidence: 99%
“…Three patients without doselimiting toxicity (dlt) were treated per cohort, in a standard 3+3 dose-escalation design: If 1 of 3 patients experienced a dlt, 3 further patients were treated at the same dose level. Cisplatin every 2 weeks was added to the treatment plan in escalating dose intensity 5 . In cohorts 1-4, the cisplatin dose was 0 mg/m 2 , 20 mg/m 2 , 30 mg/m 2 , and 40 mg/m 2 respectively, given 4 times starting at week 1 (that is, weeks 1, 3, 5, and 7).…”
Section: Chemotherapymentioning
confidence: 99%
“…Toxicities experienced by the patients included skin toxicity (rashes, dryness, erythema), weight loss, fatigue, anorexia, nausea, dehydration, gastritis, hand-foot syndrome, sepsis, hyponatremia, and hematologic events 5 Figure 1 shows the mean scores for global qol and for the functional and symptom scales at each time point. Table iii shows median differences from baseline in the scores for each domain at completion of radiation and at 4 weeks, 6-12 months, and 2-3 years after crt completion.…”
Section: Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Two-sided P values of less than 0.05 were used to assess statistical significance. MacLellan et al [12,13] have reported on recurrence outcomes. Of the 197 patients treated, 71 recurrences (36 %) were identified, of which 57 (80 %) were classified as having distant metastases as either the only site of failure Retrospective assessment of patterns of recurrence relative to radiotherapy volumes for… 889 or as a component of failure.…”
Section: Discussionmentioning
confidence: 99%